Wear-resistant composite material for data line and preparation method of wear-resistant composite material
By introducing abrasion-resistant additives with modified boron nitride surface grafted urea bonds and polyether segments into the data line composite, the problem of easy damage in the friction process of traditional materials is solved, and the wear resistance and toughness of the materials are improved, which extends the service life and reduces friction resistance.
Patent Information
- Application Number
- CN202510653556.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-08-05
AI Technical Summary
The traditional data cable is prone to scratches and cracks when repeatedly bent, plugging and friction, and contacting the rough surface, resulting in a shortened service life and a risk of short circuit. The addition of inorganic filler can easily lead to material embrittlement and flexibility.
SBS, polypropylene, maleic anhydride grafted polyethylene, and polyamide thermoplastic elastomers are used as the main raw materials, and wear-resistant additives are introduced. By modifying the surface of boron nitride grafted urea bonds and polyether segments, a lubricating film is formed to reduce the friction coefficient, enhance the interface binding force, and improve the wear resistance and toughness of the material.
It significantly improves the wear resistance and mechanical properties of the data line composite material, reduces friction resistance, extends service life and avoids the risk of short circuits.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a wear-resistant composite material for a data cable and a preparation method thereof. Background Art
[0002] With the rapid adoption and iterative upgrades of consumer electronic devices, data cables, as the core carriers connecting devices to power and signal transmission, have attracted considerable attention for their reliability, durability, and safety. However, traditional data cable sheathing materials (such as common thermoplastic elastomers (TPE), PVC, or TPU) often face severe mechanical wear in actual use. Repeated bending, plugging and unplugging friction, and contact with rough surfaces can easily lead to surface scratches, crack propagation, and even insulation rupture, seriously shortening their service life and potentially causing short circuit risks.
[0003] While traditional TPE materials offer excellent flexibility and workability, their wear resistance and mechanical strength (such as tensile strength and tear resistance) are relatively insufficient. To improve the wear resistance of composite materials, the industry generally adds inorganic fillers (such as silica, carbon black, or talc) through physical blending to enhance hardness and scratch resistance. However, excessive addition can easily lead to material embrittlement and reduced flexibility, often resulting in an imbalance in "strength-flexibility" performance, uneven filler dispersion, and poor interfacial compatibility. Therefore, improving the wear resistance of materials without sacrificing their mechanical properties is a challenge currently being explored by researchers. Summary of the Invention
[0004] In order to solve the above technical problems, the present invention provides a wear-resistant composite material for a data cable and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A wear-resistant composite material for a data cable, comprising the following raw materials in parts by weight: 25-45 parts of SBS, 8-15 parts of polypropylene, 6-10 parts of maleic anhydride grafted polyethylene, 5-10 parts of polyamide thermoplastic elastomer, 15-25 parts of white oil, 0.5-1 part of antioxidant, 1-2 parts of lubricant, and 3-6 parts of wear-resistant additive;
[0007] Furthermore, the antioxidant is antioxidant 1010, and the lubricant is zinc stearate;
[0008] The wear-resistant additive is prepared by the following steps:
[0009] Step A1: 1,3-diamino-2-propanol and hexagonal boron nitride are uniformly dispersed in water, transferred to a sand mill, zirconium oxide sand mill beads are added, sand milled, the sand mill beads are removed, the mixed solution is collected, ultrasonicated for 3 hours, centrifuged, washed, and dried to obtain modified boron nitride;
[0010] Furthermore, in step A1, the mass ratio of 1,3-diamino-2-propanol, hexagonal boron nitride, and zirconium oxide grinding beads is 4-8:2-5:200;
[0011] Furthermore, the diameter of the zirconium oxide grinding beads in step A1 is 2 mm;
[0012] Furthermore, the sand grinding treatment in step A1 is to sand grind the sand grinding jar in a sand grinder at a speed of 1500-2000 rpm for 8-12 hours;
[0013] Furthermore, the step A1 of removing the sanding beads is to sieve out the sanding beads using a 20-mesh sieve;
[0014] Step A2, uniformly stirring the modified boron nitride and sodium hydroxide in toluene, adding toluene-2,5-diisocyanate toluene solution, and heating to 70-80° C., reacting under nitrogen for 12 hours, rotary evaporation, washing, and drying to obtain isocyanate-terminated boron nitride;
[0015] Furthermore, in step A2, the ratio of modified boron nitride, sodium hydroxide, toluene and toluene-2,5-diisocyanate toluene solution is 1-3 g:0.03-0.06 g:100 mL:100 mL;
[0016] Furthermore, the toluene-2,5-diisocyanate toluene solution in step A2 is prepared by mixing toluene-2,5-diisocyanate and toluene in a ratio of 0.01-0.02 mol:100 mL;
[0017] Step A3: Mix and stir the isocyanate-terminated boron nitride and dibutyltin dilaurate in N,N-dimethylformamide, add polyethylene glycol monomethyl ether (number average molecular weight of 200), and heat to 45° C. for 2-3 hours. Filter, wash, and dry to obtain a wear-resistant additive.
[0018] Furthermore, in step A3, the usage ratio of isocyanate-terminated boron nitride, dibutyltin dilaurate, N,N-dimethylformamide and polyethylene glycol monomethyl ether is 5-10 g:0.5-2 mL:100 mL:1.5-3.5 g.
[0019] A method for preparing a wear-resistant composite material for a data cable comprises the following steps:
[0020] The raw materials are weighed by weight, and SBS, polypropylene, maleic anhydride grafted polyethylene, polyamide thermoplastic elastomer, white oil, antioxidant, lubricant and wear-resistant additive are added into a blender and stirred evenly. The mixture is then transferred to a twin-screw extruder for extrusion and granulation to obtain a wear-resistant composite material for data cables.
[0021] Beneficial effects of the present invention:
[0022] The composite material for data cables prepared by the present invention uses SBS, polypropylene, maleic anhydride grafted polyethylene and polyamide thermoplastic elastomer as main raw materials, and adds functional additives to improve the wear resistance, hardness and mechanical properties of the composite material; among them, the wear-resistant additive can not only improve the wear resistance of the composite material after being introduced into the matrix, but also improve the toughness of the matrix.
[0023] The wear-resistant additive in the present invention is based on hexagonal boron nitride, and is prepared by grafting urea bonds and polyether segments on its surface. The modification of organic molecules (urea bonds, polyether segments) improves the dispersibility of boron nitride in the matrix, and after introducing it into the matrix, the wear resistance and mechanical properties of the matrix are improved. Among them, hexagonal boron nitride can easily slide between layers during friction due to its unique layered structure, forming a lubricating film, significantly reducing the friction coefficient and reducing surface wear. The polyether segments can synergistically act with boron nitride to reduce frictional resistance and improve wear resistance. At the same time, they can also undergo reversible deformation during friction, absorb part of the impact energy, and reduce surface damage. The polar urea bonds in the matrix can form hydrogen bonds with polar components in the matrix, thereby enhancing the interfacial bonding force between the wear-resistant additive and the matrix and further improving the wear resistance of the matrix. DETAILED DESCRIPTION
[0024] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0025] Example 1: The wear-resistant additive is prepared by the following steps:
[0026] Step A1: 4 g of 1,3-diamino-2-propanol and 2 g of hexagonal boron nitride were evenly dispersed in water, transferred to a sand mill, and 200 g of 2 mm diameter zirconium oxide sand milling beads were added. The sand milling jar was then sand milled at 1500 rpm for 8 h in a sand mill. The sand milling beads were removed with a 20-mesh sieve, and the mixture was collected and ultrasonicated for 3 h. The mixture was centrifuged, washed, and dried to obtain modified boron nitride.
[0027] Step A2, 1g of modified boron nitride and 0.03g of sodium hydroxide were stirred in 100mL of toluene, 100mL of toluene-2,5-diisocyanate toluene solution was added, and the temperature was raised to 70°C, reacted under nitrogen for 12h, rotary evaporated, washed, and dried to obtain terminated isocyanate boron nitride, wherein the toluene-2,5-diisocyanate toluene solution was prepared by mixing toluene-2,5-diisocyanate and toluene in a ratio of 0.01mol:100mL;
[0028] Step A3: 5 g of isocyanate-terminated boron nitride and 0.5 mL of dibutyltin dilaurate were mixed and stirred in 100 mL of N,N-dimethylformamide, 1.5 g of polyethylene glycol monomethyl ether (number average molecular weight of 200) was added, and the temperature was raised to 45 ° C. and reacted for 2 h. The mixture was filtered, washed, and dried to obtain a wear-resistant additive.
[0029] A method for preparing a wear-resistant composite material for a data cable comprises the following steps:
[0030] 25 parts of SBS, 8 parts of polypropylene, 6 parts of maleic anhydride grafted polyethylene, 5 parts of polyamide thermoplastic elastomer, 15 parts of white oil, 10100.5 parts of antioxidant, 1 part of zinc stearate, 3 parts of wear-resistant additive;
[0031] The raw materials are weighed by weight, and SBS, polypropylene, maleic anhydride grafted polyethylene, polyamide thermoplastic elastomer, white oil, antioxidant 1010, zinc stearate and wear-resistant additive are added into a blender and stirred evenly. The mixture is transferred to a twin-screw extruder for extrusion and granulation to obtain a wear-resistant composite material for data cables.
[0032] Example 2: The wear-resistant additive is prepared by the following steps:
[0033] Step A1: 6 g of 1,3-diamino-2-propanol and 3 g of hexagonal boron nitride were evenly dispersed in water, transferred to a sand mill, and 200 g of 2 mm diameter zirconium oxide sand milling beads were added. The sand milling jar was then sand milled at 1600 rpm for 10 h in a sand mill. The sand milling beads were removed with a 20-mesh sieve, and the mixture was collected and ultrasonicated for 3 h. The mixture was centrifuged, washed, and dried to obtain modified boron nitride.
[0034] Step A2, 2g of modified boron nitride and 0.045g of sodium hydroxide were stirred in 100mL of toluene, 100mL of toluene-2,5-diisocyanate toluene solution was added, and the temperature was raised to 75°C, reacted under nitrogen for 12h, rotary evaporated, washed, and dried to obtain terminated isocyanate boron nitride, wherein the toluene-2,5-diisocyanate toluene solution was prepared by mixing toluene-2,5-diisocyanate and toluene in a ratio of 0.015mol:100mL;
[0035] Step A3: 7.5 g of isocyanate-terminated boron nitride and 1 mL of dibutyltin dilaurate were mixed and stirred in 100 mL of N,N-dimethylformamide, 2.5 g of polyethylene glycol monomethyl ether (number average molecular weight of 200) was added, and the temperature was raised to 45 ° C. The reaction was carried out for 2.5 hours, filtered, washed, and dried to obtain a wear-resistant additive.
[0036] A method for preparing a wear-resistant composite material for a data cable comprises the following steps:
[0037] 30 parts of SBS, 10 parts of polypropylene, 8 parts of maleic anhydride grafted polyethylene, 7 parts of polyamide thermoplastic elastomer, 20 parts of white oil, 0.75 parts of antioxidant 1010, 1.5 parts of zinc stearate, 4 parts of wear-resistant additive;
[0038] The raw materials are weighed by weight, and SBS, polypropylene, maleic anhydride grafted polyethylene, polyamide thermoplastic elastomer, white oil, antioxidant 1010, zinc stearate and wear-resistant additive are added into a blender and stirred evenly. The mixture is transferred to a twin-screw extruder for extrusion and granulation to obtain a wear-resistant composite material for data cables.
[0039] Example 3: The wear-resistant additive is prepared by the following steps:
[0040] Step A1: 7 g of 1,3-diamino-2-propanol and 4 g of hexagonal boron nitride were evenly dispersed in water, transferred to a sand mill, and 200 g of 2 mm diameter zirconium oxide sand milling beads were added. The sand milling jar was then sand milled at 1800 rpm for 10 h in a sand mill. The sand milling beads were removed with a 20-mesh sieve, and the mixture was collected and ultrasonicated for 3 h. The mixture was centrifuged, washed, and dried to obtain modified boron nitride.
[0041] Step A2, 2.5g of modified boron nitride and 0.05g of sodium hydroxide were stirred in 100mL of toluene, 100mL of toluene-2,5-diisocyanate toluene solution was added, and the temperature was raised to 80°C, reacted under nitrogen for 12h, rotary evaporated, washed, and dried to obtain terminated isocyanate boron nitride. The toluene-2,5-diisocyanate toluene solution was prepared by mixing toluene-2,5-diisocyanate and toluene in a ratio of 0.02mol:100mL;
[0042] Step A3: 8.5 g of isocyanate-terminated boron nitride and 1.5 mL of dibutyltin dilaurate were mixed and stirred in 100 mL of N,N-dimethylformamide, 3 g of polyethylene glycol monomethyl ether (number average molecular weight of 200) was added, and the temperature was raised to 45° C. for reaction for 3 h. The mixture was filtered, washed, and dried to obtain a wear-resistant additive.
[0043] A method for preparing a wear-resistant composite material for a data cable comprises the following steps:
[0044] SBS 40 parts, polypropylene 12 parts, maleic anhydride grafted polyethylene 8 parts, polyamide thermoplastic elastomer 8 parts, white oil 20 parts, antioxidant 10100.8 parts, zinc stearate 1.5 parts, wear-resistant additive 5 parts;
[0045] The raw materials are weighed by weight, and SBS, polypropylene, maleic anhydride grafted polyethylene, polyamide thermoplastic elastomer, white oil, antioxidant 1010, zinc stearate and wear-resistant additive are added into a blender and stirred evenly. The mixture is transferred to a twin-screw extruder for extrusion and granulation to obtain a wear-resistant composite material for data cables.
[0046] Example 4: The wear-resistant additive is prepared by the following steps:
[0047] Step A1: 8 g of 1,3-diamino-2-propanol and 5 g of hexagonal boron nitride were evenly dispersed in water, transferred to a sand mill, and 200 g of 2 mm diameter zirconium oxide sand milling beads were added. The sand milling jar was then sand milled at 2000 rpm for 12 h in a sand mill. The sand milling beads were removed with a 20-mesh sieve, and the mixed solution was collected and ultrasonicated for 3 h. The mixture was centrifuged, washed, and dried to obtain modified boron nitride.
[0048] Step A2, 3g of modified boron nitride and 0.06g of sodium hydroxide were stirred in 100mL of toluene, 100mL of toluene-2,5-diisocyanate toluene solution was added, and the temperature was raised to 80°C, reacted under nitrogen for 12h, rotary evaporated, washed, and dried to obtain terminated isocyanate boron nitride, wherein the toluene-2,5-diisocyanate toluene solution was prepared by mixing toluene-2,5-diisocyanate and toluene in a ratio of 0.02mol:100mL;
[0049] Step A3: Mix 10 g of isocyanate-terminated boron nitride and 2 mL of dibutyltin dilaurate in 100 mL of N,N-dimethylformamide and stir evenly. Add 3.5 g of polyethylene glycol monomethyl ether (number average molecular weight of 200), heat to 45 ° C and react for 3 h. Filter, wash, and dry to obtain a wear-resistant additive.
[0050] A method for preparing a wear-resistant composite material for a data cable comprises the following steps:
[0051] 45 parts of SBS, 15 parts of polypropylene, 10 parts of maleic anhydride grafted polyethylene, 10 parts of polyamide thermoplastic elastomer, 25 parts of white oil, 10101 parts of antioxidant, 2 parts of zinc stearate, 6 parts of wear-resistant additive;
[0052] The raw materials are weighed by weight, and SBS, polypropylene, maleic anhydride grafted polyethylene, polyamide thermoplastic elastomer, white oil, antioxidant 1010, zinc stearate and wear-resistant additive are added into a blender and stirred evenly. The mixture is transferred to a twin-screw extruder for extrusion and granulation to obtain a wear-resistant composite material for data cables.
[0053] Comparative Example 1: This comparative example is a wear-resistant composite material for a data cable. The difference from Example 4 is that no wear-resistant additive is added, and all other aspects are the same.
[0054] Comparative Example 2: This comparative example is a wear-resistant composite material for a data cable. The difference from Example 4 is that hexagonal boron nitride is used instead of the wear-resistant additive, and the rest are the same.
[0055] Comparative Example 3: This comparative example is a wear-resistant composite material for a data cable. The difference from Example 4 is that the wear-resistant additive is replaced by commercially available wear-resistant agent silica, and the rest are the same.
[0056] The performance of the data cables prepared in Examples 1-4 and Comparative Examples 1-3 was tested using the wear-resistant composite materials:
[0057] Hardness test: Test the Shore A hardness of composite materials according to GB / T 2411-2008;
[0058] Wear resistance test: Test the wear resistance of composite materials according to GB / T 1689-2014;
[0059] Elongation at break test: Test the elongation at break of composite materials in accordance with GB / T 1040.2-2006;
[0060] The test results are shown in Table 1:
[0061] Table 1: Performance test results
[0062] Shore A hardness <![CDATA[Wear amount (mm 3 )]]> Elongation at break (%) Example 1 68.3 91 399.6 Example 2 68.8 89 405.8 Example 3 69.2 88 408.2 Example 4 69.7 87 411.7 Comparative Example 1 61.3 129 353.3 Comparative Example 2 64.8 118 359.1 Comparative Example 3 65.2 113 363.4
[0063] As can be seen from Table 1, the wear-resistant composite material for data cables prepared by the present invention has excellent hardness, wear resistance and mechanical properties after being tested for hardness, wear resistance and elongation at break.
[0064] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the scope of protection of the present invention.
Claims
1. A wear-resistant composite material for a data cable, characterized in that: The invention comprises the following raw materials in parts by weight: 25-45 parts of SBS, 8-15 parts of polypropylene, 6-10 parts of maleic anhydride grafted polyethylene, 5-10 parts of polyamide thermoplastic elastomer, 15-25 parts of white oil, 0.5-1 part of antioxidant, 1-2 parts of lubricant, and 3-6 parts of wear-resistant additive; The wear-resistant additive is prepared by reacting terminal isocyanate boron nitride and polyethylene glycol monomethyl ether, the terminal isocyanate boron nitride is prepared by reacting modified boron nitride and toluene-2,5-diisocyanate, and the modified boron nitride is prepared by sand-milling 1,3-diamino-2-propanol and hexagonal boron nitride.
2. The wear-resistant composite material for data cables according to claim 1, characterized in that: The wear-resistant additive is prepared by the following steps: Step A1: 1,3-diamino-2-propanol and hexagonal boron nitride are uniformly dispersed in water, transferred to a sand mill, zirconium oxide sand mill beads are added, sand milled, the sand mill beads are removed, the mixed solution is collected, ultrasonicated for 3 hours, centrifuged, washed, and dried to obtain modified boron nitride; Step A2, uniformly stirring the modified boron nitride and sodium hydroxide in toluene, adding toluene-2,5-diisocyanate toluene solution, and heating to 70-80° C., reacting under nitrogen for 12 hours, rotary evaporation, washing, and drying to obtain isocyanate-terminated boron nitride; Step A3: Mix and stir the isocyanate-terminated boron nitride and dibutyltin dilaurate in N,N-dimethylformamide, add polyethylene glycol monomethyl ether, and heat to 45° C. for 2-3 hours. Filter, wash, and dry to obtain a wear-resistant additive.
3. The wear-resistant composite material for data cables according to claim 2, characterized in that: In step A1, the mass ratio of 1,3-diamino-2-propanol, hexagonal boron nitride and zirconium oxide sand grinding beads is 4-8:2-5:
200.
4. The wear-resistant composite material for data cables according to claim 2, characterized in that: The diameter of the zirconium oxide sand grinding beads in step A1 is 2 mm. The sand grinding treatment is to sand the sand grinding jar in a sand grinding machine at a speed of 1500-2000 rpm for 8-12 hours. The sand grinding beads are removed by sieving out the sand grinding beads with a 20-mesh sieve.
5. The wear-resistant composite material for data cables according to claim 2, characterized in that: In step A2, the usage ratio of modified boron nitride, sodium hydroxide, toluene and toluene-2,5-diisocyanate toluene solution is 1-3 g:0.03-0.06 g:100 mL:100 mL.
6. The wear-resistant composite material for data cables according to claim 2, characterized in that: The toluene-2,5-diisocyanate toluene solution in step A2 is prepared by mixing toluene-2,5-diisocyanate and toluene in a ratio of 0.01-0.02 mol:100 mL.
7. The wear-resistant composite material for data cables according to claim 2, characterized in that: In step A3, the amount ratio of isocyanate-terminated boron nitride, dibutyltin dilaurate, N,N-dimethylformamide and polyethylene glycol monomethyl ether is 5-10 g:0.5-2 mL:100 mL:1.5-3.5 g.
8. The wear-resistant composite material for data cables according to claim 1, characterized in that: The antioxidant is antioxidant 1010, and the lubricant is zinc stearate.
9. A method for preparing the wear-resistant composite material for data cables according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed by weight, and SBS, polypropylene, maleic anhydride grafted polyethylene, polyamide thermoplastic elastomer, white oil, antioxidant, lubricant and wear-resistant additive are added into a blender and stirred evenly. The mixture is then transferred to a twin-screw extruder for extrusion and granulation to obtain a wear-resistant composite material for data cables.